Aplikasi Absensi Siswa Berbasis Android - Gito Ardiansyah; Rozali Toyib (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Students at SMA Negeri 1 Central Bengkulu are still dominated by the manual method, namely taking student absences by recording them on paper which will later be summarized from each student's attendance data. Because the manual recap of student attendance data also affects the information about attendance recaps which is still limited to the school, so parents/guardians cannot monitor student attendance levels. Inconsistency in attendance data can be detrimental to students, there is often a difference between the absences listed in the attendance register book/record into the system, which is one of the factors that makes the original data and data that have been verified into the system different. Utilizing the location of an Android smartphone to become an attendance system, which functions to provide location information based on the user's nearest location, assisting in searching for locations based on 6 existing parameters, namely education (high school/vocational school/university), hospital, hotel, restaurant, tourist attraction , and malls/traditional markets. It is hoped that this application will always be up to date so that this application follows developments in Android-based lecturer/teacher attendance information technology using the Flutter framework.